The toys$1 (Bpartys - Hunt, Roderick (Oxford Oxford university press, 2011)
Kipper decides to make a party for his toys. He mixes all sorts of unusual things into a cake$1 (Blike cornflakes, tomato sauce, and jam! When the (3z(Bcake(3y (Bis ready, it turns out to be a big, sticky mess. In the end, instead of enjoying the party, Kipper has to clean everything up.s
Kipper makes a messy cake for his toys$1 (Bparty using odd ingredients, but ends up having to clear up instead of celebrating.s
Keywords: English